Puberty Period among Different Religions, Traditions, and Societies - Obaid, Ali Fadhil; Kadim, Maha Ahmed; Abdulrasol, Zainab Abdulameer; Al-Abbass, Hussein Ali Abd; Hussein, Mohammed Abbas (South Asian Journal of Social Sciences and Humanities, 2022)
Abstract: Puberty is an important stage of human life. Several physiological alterations accompanying the teenage years manifest themselves in often complex and curious means to which females show different reactions. Even though this stage of a female’s life is normal, it is often associated with some degree of suffering and embarrassment, it is mainly due to a sense of hesitation. The main event of puberty is the onset of the menstrual cycle; menstruation is a normal physiological process that has been distorted and damaged with negative connotations. Many religions around the world have set expectations for females during their menstrual period. This paper discusses how females during puberty must behave and be seen in many religions. Additionally, it drives debates on how different societies treat and view females during the menstrual period. Adolescent girls must be educated on how to go about the topics surrounding puberty, and the normal physiological changes that happen during the period at school. Societies, families, and teenagers themselves are responsible for working together to create an environment in which accurate info on puberty and related subjects is readily available.